Evaluasi Kapabilitas Layanan SAMBAT Online menggunakan COBIT 5 - Ade Renata; Andi Reza Perdanakusuma; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Sistem Aplikasi Masyarakat Bertanya Terpadu (SAMBAT) Online is one of the electronic services (based on information technology) at the Communication and Information Technology Office of Malang City which still often experiences technical problems rooted in information technology governance issues. Based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 5 of 2018 concerning Guidelines for Evaluation of Electronic-Based Government Systems, which states that the SPBE evaluation is the result of absorption from COBIT, this study tries to assess service governance using the COBIT 5 domain DSS (Deliver) framework. , Service and Support) with a focus area on the DSS03 (Manage Problems) process. This study aims to determine the capability level and gap and provide recommendations. The result of the capability level in the DSS03 process is 1 with a gap of 1. The recommendations given are in the form of a road map using ITIL V3 2011 as a guide.